Pengaruh Desain Kerja dan Budaya Organisasi Terhadap Komitmen Organisasi Dalam Meningkatkan Kinerja Karyawan Pada PT Ongkowidjojo Malang - Muhammad Ilham Bachraesy; Siti Asiyah; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the direct effect of job design, organizational culture and organizational commitment on employee performance and organizational commitment as a mediating variable. Based on data from PT Ongkowidjojo Malang, there are 350 employees as a population, so the sample used in the study was 78 employees. The sampling method used was purposive sampling method. In this study, the analysis technique used is multiple linear regression using cross section data. Based on the results of path analysis and research results, it is known that job design has a positive and significant effect on organizational commitment and organizational culture has a positive and significant effect on organizational commitment. Job design has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, and organizational commitment has a positive and significant effect on employee performance. Organizational commitment can mediate the influence of job design and organizational culture on employee performance. Keywords: Job design, organizational culture, organizational commitment, and employee performance